Demographic profiles and care management of children with spina bifida in Zambia - Faith Banda; Nondwe Mlenzana; Margaret M. Mweshi; Loveness A. Nkhata (Rehabilitation Advances in Developing Health Systems, 2025)
Background: Spina bifida (SB), a major neural tube defect (NTD), is a leading cause of childhood disability in sub-Saharan Africa, with rising incidence in Zambia. It poses complex medical challenges requiring multidisciplinary care; yet, there is limited demographic and prevalence data on the same, particularly in Zambia.